Sosialisasi Bahaya Ketuban Pecah Dini Pada Ibu Bersalin di Desa Bangun Rejo Kecamatan Tanjung Morawa Kabupaten Deli Serdang - Ika Damayanti Sipayung; Ridesman Ridesman; Riska Susanti Natalia Pasaribu; Lasria Yolivia Aruan; Angelina Br Simbolon (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2022)
A One of the causes of the still high maternal morbidity and mortality rate is premature rupture of the membranes. Premature rupture of membranes is the rupture of the membranes before there are signs of labor and wait one hour before the start of labor. The incidence of premature rupture of membranes is close to 10% of all deliveries. Method: educating pregnant women about the danger signs of pregnancy by using leaflets. Results: Participants in this activity were 20 pregnant women in Sumber Rejo Village. In its implementation, the objectives are explained about the dangers of premature rupture of membranes, benefits, how to detect danger signs of premature rupture of membranes. Next, explain when the mother is giving birth to immediately check her pregnancy if she feels complaints about her pregnancy. Conclusion: community service activities are carried out based on counseling. Service activities carried out for 3 months. The results of this Community Service regarding danger signs of premature rupture of membranes. This community service has been carried out from August to September 2022 to be precise for 3 months.